(untitled) (Bioscience Journal, 2022)
Cultivating native fruit species depends on the existence of technical and scientific information. In this context, studies on propagation are the basis for other investigations. Campomanesia adamantium is propagated by seeds, and quality seeds guarantee the formation of high-performance plants in the field. This study aimed to analyze the dehydration tolerance and storage sensitivity of Campomanesia adamantium seeds. Experiment 1 evaluated the physiological quality of seeds with moisture contents of 43, 30, 26, 23, 18, 15, and 5%. Experiment 2 determined the seed moisture content, germination, and vigor of seeds depulped and immediately stored at 16 and 25°C, for 25 and 50 days. Seed viability was not affected by dehydration up to 15% of moisture content but decreased at 5%. Drying was accompanied by reduced seed vigor and seedling mass. The germination of unstored seeds was superior to stored ones. Storage at 16°C for 25 days was promising to maintain seed viability. The seeds showed intermediate recalcitrant behavior. Dehydration below 30% reduced vigor, while 5% affected viability. Campomanesia adamantium seeds can be stored for 25 days at 16°C in permeable packaging that maintains approximately 10% of moisture, with germination higher than 60%.